ChemInform Abstract: Metal‐Free Oxidative Arylphosphination of Activated N‐Substituted‐N‐arylacrylamide Derivatives Using K2S2O8. Issue 33 (19th August 2014) - Li, Ya‐Min; Shen, Yuehai; Chang, Kwen‐Jen; Yang, Shang‐Dong
Abstract Only diphenylphosphine oxide reacts with acrylamides in the presence of K2S2O8.